Can green finance improve carbon emission efficiency? Evidence from China - Liang, Jinhao; Song, Xiaowei (Frontiers in Environmental Science, 2022)
The improvement of carbon emission efficiency and the realization of the goal of “carbon peaking and carbon neutrality” are the key issues that China needs to solve urgently at this stage. The green and low-carbon transformation of the economy requires sufficient financial support. Whether green finance is an opportunity to improve China’s carbon emission efficiency is worth studying. For the aim, based on the macro-panel data of 30 provinces in China from 2010 to 2019, this paper uses fixed effect model and spatial Durbin model to study the impact of green finance on regional carbon emission efficiency. The results show that: First, the development of green finance can improve the carbon emission efficiency; Second, in addition to the “local effect”, the influence of green finance on carbon emission efficiency has a “neighborhood effect”, that is, it has a spatial spillover effect on carbon emission efficiency in neighboring areas, and this effect only exists in a short time; Third, the impact of green finance on carbon emission efficiency is heterogeneous in different regions with different environmental regulations. This paper has reference significance for green finance development and the implementation of the goal of “carbon peaking and carbon neutrality” in China.